2019
DOI: 10.29392/joghr.3.e2019015
|View full text |Cite
|
Sign up to set email alerts
|

Exploring causal pathways for factors associated with neonatal, infant and under-five mortality, analysis of 2015-2016 Myanmar Demographic Health Survey

Abstract: Background Background This study explores the intermediate and proximate causal factors associated with under-five mortality in Myanmar in order to help policymakers to assess and formulate appropriate interventions to prevent neonatal, infant and under-five deaths. Methods Methods We examined the data from the 2015-2016 Myanmar Demographic and Health Survey. The study population consisted of 4198 live born singleton children born within five years prior to the survey. We used logistic binomial regression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…In this study, the likelihood of under-5 mortality was higher among single and cohabiting mothers compared with married mothers. Similar findings have been obtained in studies that have been conducted in SSA6 51 52 and other low-income countries 53 54. Most of these studies have cited lack of spousal support as the major reason for the high prevalence of under-5 mortality among children born to single and cohabiting women 6 51 52.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, the likelihood of under-5 mortality was higher among single and cohabiting mothers compared with married mothers. Similar findings have been obtained in studies that have been conducted in SSA6 51 52 and other low-income countries 53 54. Most of these studies have cited lack of spousal support as the major reason for the high prevalence of under-5 mortality among children born to single and cohabiting women 6 51 52.…”
Section: Discussionsupporting
confidence: 82%
“…However, neonatal mortality was not significantly associated with SFU and exposure to IAP, and these results are consistent with previous research conducted in LMICs (17,39). Several biological factors, such as low birth weight, prematurity, and complications associated with pregnancy and delivery, might be responsible for the null association between IAP and neonatal mortality (20,30,40). Additionally, breastfeeding could work as a protective factor diminishing the effect of IAP on neonatal mortality.…”
Section: Exposuressupporting
confidence: 88%
“…Evidence suggests that the combustion of SFU emits multiple pollutants such as fine particles, carbon monoxide, formaldehyde, and many more toxic chemicals, which increase the risk of mortality from ALRIs, asthma, and pneumonia among infant and young children exposed to these pollutants (3,6,7,(23)(24)(25)(26)(27)(28)(29). Exposure to these toxic pollutants also increases the risk of low birth weight, stillbirth, and preterm birth, including acute and chronic health problems, all of which are considered as leading causes of child mortality (20,22,30,31).…”
Section: Exposuresmentioning
confidence: 99%
“…Previous research has also shown higher mortality rates in rural areas of Pakistan, attributed to a number of causes including larger household sizes in rural areas 23 , 24 and low coverage of modern family planning methods and health services. 25 The finding of higher mortality rates among children of multiparous women in our survey is also consistent with other findings.…”
Section: Discussionmentioning
confidence: 98%